FAKTOR PENENTU INEFISIENSI TEKNIS PADA USAHA TERNAK KAMBING PERANAKAN ETTAWA - Siti Maemunah; Agus Yuniawan Isyanto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2017)
The study was conducted with the aim to find out the determinants of technical inefficiency in PE goat livestock farming. The study was conducted using case study on As-Salam Agribusiness Group in Sirnagalih Village, Indihiang Sub-district, Tasikmalaya City. Group members of 26 peoples were taken entirely as samples or conducted by census. The data obtained were analyzed by using multiple regression equation where parameter estimation was done by using SPSS 16. The results showed that the determinants of technical inefficiency in PE goat livestock farming were age, education, number of livestock ownership, family size and credit.